Strategi Pustakawan dalam Meningkatkan Citra Perpustakaan Sutan Tagor Mulia Padangsidimpuan - Siregar, Nisya; Sazali, Hasan; Purwaningtyas, Franindya (VISA: Journal of Vision and Ideas, 2024)
This research discusses library strategies in improving the image of the Sutan Tagor Mulia Padangsidimpuan Library. The goal of this research is to find out how library strategies can enhance the image of the Sutan Tagor Mulia Padangsidimpuan Library. This research uses a descriptive method with a qualitative approach. Data collection techniques include observation, interviews, and documentation. The informants in this research are librarians at the Sutan Tagor Mulia Padangsidimpuan Library. The results show that the librarians at the Sutan Tagor Mulia Padangsidimpuan Library implement image enhancement strategies, such as: a) Optimizing services, b) Conducting socialization, c) Arranging reading spaces, and d) Developing collection materials. The librarians' strategies in improving the library's image aim to enhance the quality of the library and receive positive feedback from visitors at the Sutan Tagor Mulia Padangsidimpuan Library.